Flood Impact Mitigation and Resilience Enhancement 2020
DOI: 10.5772/intechopen.93069
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Technical Advances in Flood Early Warning Systems (FEWSs)

Abstract: Flood early warning systems (FEWSs)—one of the most common flood-impact mitigation measures—are currently in operation globally. The UN Office for Disaster Risk Reduction (UNDRR) strongly advocates for an increase in their availability to reach the targets of the Sendai Framework for Disaster Risk Reduction and Sustainable Development Goals (SDGs). Comprehensive FEWS consists of four components, which includes (1) risk knowledge, (2) monitoring and forecasting, (3) warning, dissemination, and communication, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…The image receives an arrow in every pixel by repeating this technique for every pixel in the image. These arrows are known as gradients, and they indicate the transition of light to dark throughout the whole image [11][12][13][14][15][16][17][18][19][20]. The upper right most section of the pie charts shows the flood duration in days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The image receives an arrow in every pixel by repeating this technique for every pixel in the image. These arrows are known as gradients, and they indicate the transition of light to dark throughout the whole image [11][12][13][14][15][16][17][18][19][20]. The upper right most section of the pie charts shows the flood duration in days.…”
Section: Resultsmentioning
confidence: 99%
“…Weather radars and remotely sensed rainfall have the potential to improve watershed monitoring by providing geographical, real-time, or near real-time data. However, the data they supply is of lesser quality than observed data, and these approaches are too young to have long enough time series to develop credible hydrological models [17].…”
Section: Flood Management Systemmentioning
confidence: 99%
“…Furthermore, with the advent of social media, authorities need to also utilise the power embedded in such networks to improve risk management while also putting some safeguards in place to avoid the spread of false information. Mitigation can also be enhanced through the integration of artificial intelligence (AI), remote sensing and social media (Perera et al 2020 ), for example, the use of AI-related tools such as artificial neural networks (ANNs) and fuzzy inference systems (FISs) (Nur Adli Zakaria et al 2021 ). These tools have extensively been used to monitor river levels, therefore presenting an opportunity for authorities to tap into their power as mitigation tools in reducing flood negative impacts.…”
Section: Complementary Flood Mitigation Tools: Social Media and Artif...mentioning
confidence: 99%
“…Such information systems for flood warning and response systems should offer hazard detection, forecasting, warnings, and responses [15]. A study of global early warning systems within developed and developing countries [16,17] has found that the availability of such technology platforms is an important factor that influences the effectiveness of early warning systems in addition to policy, institutional, and societal factors.…”
Section: Introductionmentioning
confidence: 99%